Tenth Five Year Plan 2002-2007 Volume-I Dimensions and Strategies - Planning Commission, Government of India (Planning Commission, Government of India, 2002)
The Tenth Five Year Plan, covering the period 2002-03 to 2006-07 represents but another step in the evolution of development planning in India. In the 55 years that have passed since our Independence, the challenges, the imperatives and the capabilities of the nation have undergone profound changes. The planning methodologies have attempted to keep pace with the emerging requirements and to guide the economy through the vicissitudes of national and global events, with greater or lesser success. The Tenth Plan carries on this tradition in the context of the objective realities of Indian economic life as they are manifested today.
Planning Commission Government of India
Planning Commission, Government of India
Keywords: Tenth Five Year Plan- India; Economic and Social Development